Diffractive imaging of a rotational wavepacket in nitrogen molecules with femtosecond megaelectronvolt electron pulses - Jie Yang (Nature Portfolio, 2016)
Imaging changes in molecular geometries with sufficient temporal and spatial resolution to image nuclei is a critical challenge in the chemical sciences. Here the authors report gasphase Megaelectronvolt electron diffraction with 100 fs temporal resolution and subAngstrom spatial resolution.